2020
DOI: 10.1007/s10597-020-00578-8
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Severity, Self-efficacy and Treatment-Seeking for Mental Health Among US Iraq/Afghanistan Military Veterans

Abstract: Military veterans have high rates of mental health problems, yet the majority do not seek treatment. Understanding treatmentseeking in this population is important. This study investigated if symptom severity and self-efficacy are associated with treatment-seeking among US Iraq/Afghanistan veterans. Survey data from 525 veterans meeting clinical criteria for PTSD and depression were included of which, 54.4% had sought treatment in the past 12 months. Multivariate logistic regression analysis indicated that hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…showing that lower versus higher self-efficacy was associated with seeking treatment (Jackson et al, 2007;Keeling et al, 2020), and others finding no association (Andersson et al, 2014). More investigation is needed of the relationship between self-efficacy and differ- medication can help their depressive condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showing that lower versus higher self-efficacy was associated with seeking treatment (Jackson et al, 2007;Keeling et al, 2020), and others finding no association (Andersson et al, 2014). More investigation is needed of the relationship between self-efficacy and differ- medication can help their depressive condition.…”
Section: Discussionmentioning
confidence: 99%
“…In a sample cross-national sample of first-year college students, Ebert et al (2019) found attitudinal barriers to be more common Previous research has shown inconsistencies in the effects of self-efficacy on treatment-seeking behaviors, with some studies showing that lower versus higher self-efficacy was associated with seeking treatment (Jackson et al, 2007;Keeling et al, 2020), and others finding no association (Andersson et al, 2014). Table 2 for display purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administrative barriers and skepticism about the treatment's effectiveness have also emerged as hindering treatment seeking (Hom et al, 2017 ; Vogt et al, 2014 ). Support of family and friends (Hom et al, 2017 ) and perceived self‐efficacy (Keeling et al, 2020 ) were both positively associated with seeking mental health care. Positive or negative views about help seeking as described above (Clark et al, 2018 ), revealed differences between combat and noncombat soldiers.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, researchers have identified several factors that are associated with underutilization of mental health services, including mental health symptomology, past help-seeking behavior, and certain sociodemographic variables. For example, symptom severity in certain mental illnesses, such as major depression, has been associated with help-seeking behaviors (e.g., Keeling et al, 2020;Kleinberg et al, 2013). In addition, previous counseling experience has been positively associated with attitudes toward seeking professional psychological help (Vogel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%